Intrathecal Immunoglobulin A Synthesis in Multiple Sclerosis: From Biological Aspects to Clinical Relevance - Dariia Kliushnikova; Ferdinand Otto; Georg Pilz; Peter Wipfler; Andrea Harrer (Biomolecules)
Intrathecal immunoglobulin A (IgA) synthesis in multiple sclerosis (MS) has long earned little attention, despite a potential significance in disease pathogenesis and prognosis. The presence of IgA-positive plasma cells in MS lesions and along damaged axons suggests a role in disease pathogenesis. Available clinical evidence about a potential positive or negative prognostic role is scarce and inconclusive. Recent observations, however, highlight the migration of immune regulatory IgA-producing plasma cells from the gut to the central nervous system (CNS) in experimental autoimmune encephalitis models. A connection between intrathecal IgA synthesis and the gut–brain axis in MS was further corroborated by the discovery of gut microbiota-specific IgA+ B cells in human CNS during relapse. In this review, we summarize current evidence on the occurrence and immunopathology of intrathecal IgA synthesis in MS, explore its biological implications, and address methodological challenges regarding the detection of IgA as a major limitation and possible source of inconsistencies in clinical studies. By synthesizing these diverse lines of evidence, we highlight the importance of further research and the need for standardized detection methods to clarify the role of IgA in MS pathogenesis, disease progression, and as potential biomarker.